Developing Leadership Competencies Framework and Measurement for Malaysian Higher Education Institutions (HEIs) (S/O 13605) - Johari, Johanim; Yahya, Khulida Kirana; Mohd Shamsudin, Faridahwati; Tan, Fee Yean (UUM, 2021)
The objectives of the study are to identify the competencies of institutional leaders in higher education institutions (HEIs) in Malaysia and to develop a framework on institutional leadership competencies of HEIs in the Malaysian context. Secondary data from extensive literature review was conducted to identify competencies of institutional leaders in HEIs. Primary data were gathered from respondents that comprises of institutional leaders and faculty members in HEIs. Questionnaires and interviews were used to gather data from respondents. Items on institutional leadership competencies were developed and tested for content and construct validity. Based on the statistical analyses, institutional leadership competencies comprised of three dimensions namely achieving goals and outcomes, leadership and leading change, and integrity and justice. The study has provided theoretical ramifications in the field of leadership in HEIs, particularly in the Malaysian context. Most importantly, this study managed to produce a framework and measurement for institutional leadership competencies for HEIs in Malaysia.